Direct Construction of Catechol Lignin for Engineering Long‐Acting Conductive, Adhesive, and UV‐Blocking Hydrogel Bioelectronics. Issue 5 (11th March 2021) - Qian, Yong; Zhou, Yijie; Lu, Mingjin; Guo, Xiaoshuang; Yang, Dongjie; Lou, Hongming; Qiu, Xueqing; Guo, Chuan Fei
Abstract: Long‐active conductivity, adhesiveness, and environmental stability are essential in the applications of hydrogel electronics. Integrating different functional materials into one system suffers from compatibility and cost problems. Inspired by the unique o‐methoxyl structure in polyphenol lignin and its binding role in plants, catechol lignin (DAL) is constructed by one‐step demethylation, which endows the lignin with a mussel‐like bioadhesion, good reducibility, as well as a high ultraviolet absorption. The DAL is then applied to reduced graphene oxide, and the products—the oxidized DAL and the reduced graphene oxide mixture (DAL/rGO) is added into a sodium alginate/polyacrylamide (SA/PAM) double network hydrogel. Based on the Schiff base reaction between the quinone of the oxidized DAL and the amino of the skin, the DAL/rGO incorporated hydrogels could stably adhere to the skin, and sensitively respond to physiological signals. In addition, the DAL could provide the hydrogels with long‐active sunscreen property when applied to real skin. These DAL based hydrogels have potential for on‐skin sensing and outdoor sport equipment. Abstract : One‐step catechol modification endows botanical‐binding lignin with mussel‐like bioadhesion, good reducibility, as well as high ultraviolet absorption. The dosage of the catechol lignin/graphene oxide redox product effectively improves the adhesion, conductivity, and UV‐blocking of double network hydrogel bioelectronics, thus enabling stable applications.